Finance and Development, June 1979. (Finance and Development; Finance and Development ;, 1979)
This paper highlights that in the first quarter of 1979, the IMF took further steps to enhance its ability to promote orderly world economic growth with reasonable price stability as a means of achieving a stable system of exchange rates. It adopted several measures designed to make the special drawing right the principal reserve asset in the world monetary system. The Interim Committee reaffirmed these aims, expressing broad support for measures that the IMF's Executive Board has adopted, or is actively considering, in furthering these goals.